Modelling of gas-liquid flow and structural interaction in bends - Nangi, Ebughni Okoria (2024)
The combined flow of gas and liquid is known to be unstable due to the fluctuations of void fraction, velocity, phase density, pressure, and momentum flux. These local fluctuations induced fluctuating forces on pipe bend and other pipe elements. In the production of oil and gas, these fluctuating gas-liquid flows are transported from reservoirs before separation. The transported fluids are often polluted with entrained sand particles. For intermittent gas liquid flow, the combine effect of flow fluctuations and particle erosion resulting from particle entrainment poses severe flow assurance challenge. This work investigates the structures and characteristics of gas-liquid intermittent flow through vertical-horizontal 90° bend, using series of CFD studies. New CFD data are generated for the evolution of cap bubble, slug, and churn flow, and induced fluctuating forces at bend using a new-inlet boundary condition and the VOF model. The DPM model is employed to model particle entrainment and k − ε model for the turbulence modelling. The numerical study has been conducted using liquid viscosities of 0.005 Pa s, 0.64 Pa s and 0.135 Pa s on a vertical horizontal 90° bend of 0.067 m ID with a riser and horizontal length of 3 m for three bend curvature radius (1.5D, 3D and 5D). The CFD studies comprises of 48 data matrix for gas and liquid superficial velocities of 0.1 m/s to 5.5 m/s and 0.3 m/s to 0.75 m/s, respectively. CFD studies are validated against experimental data, and they show good agreement. The new inlet boundary condition produces reliable slug flow characterised by the axial movement of bullet-shaped gas bubbles, interspersed by liquid slugs which contain smaller dispersed bubbles. The result of the simulation study of the structural evolution of gas-liquid flow across the 90° bend shows several scenarios depending on the flow regime approaching the bend and the flow rates of the phases at the inlet. Plug, stratified, slug and stratified wavy flow are observed after the bend for cap bubble, slug, and churn flow before the bend. The spectrum analysis of the time histories of the cross-sectional gas volume fraction indicates that the gas bubbles are chiefly responsible for the flow fluctuations in intermittent gas liquid flows. The fluctuating forces acting on the pipe bend due to the internal gas liquid flow increases with both gas and liquid superficial velocity. However, the magnitude of the root mean square force Frms depends on the flow regime. The erosion studies shows that particle entrainment in gas-liquid flow depends on the liquid volumetric fraction.